A importância da cultura alimentar no Vale do Paraíba Paulista - Ribeiro, Maria Luiza Rocha (2020)
This dissertation proposition is to develop the debate through a bibliographical research and a historical approach grounded in the oral history, using as research instruments: recipe books, photographs and stories of the descendants at shows the country culture presents in the Vale do Paraiba, North of Sao Paulo, Brazil. It deals with the hypothesis of existence of the hillbilly man and search through the customs and traditions, perpetuated in time, to accentuate the aspects that prove the continuity of this culture, in the 21th century. It addresses the relationship between the “caipira” man and food in history context of the region through the years of it building, and then, summarizing the relevance of this cultural exchange in the food culture construction of Vale do Paraiba in Sao Paulo. Using as theoretical basis, the concept of food is culture introduced by Montanari (2013), the understanding of the Brazilian's cuisine formation by Dória (2014), the countryside's food in the state of São Paulo by Candido (2017), approaching the methodological’s concept of the oral history by Thompson (1998 e 2002), besides the historical concept related by other researchers like Motta Sobrinho (1978). Finally, to clarify that country culture and Vale do Paraíba are amalgamated. The region has suffered many influences from other cultures and appropriated of them. The way of being and existing in this country culture is still lived inside the houses of these people, but they don’t accept the title “caipira” because the image of this man still is very derogatory between them. That’s why they don't want to be related as “caipira”.